Combined inhibition of PARP and EZH2 for cancer treatment: Current status, opportunities, and challenges - Zhang, Xi; Huo, Xiao; Guo, Hongyan; Xue, Lixiang (Frontiers in Pharmacology, 2022)
Tumors with BRCA1/2 mutations or homologous recombination repair defects are sensitive to PARP inhibitors through the mechanism of synthetic lethality. Several PARP inhibitors are currently approved for ovarian, breast and pancreatic cancer in clinical practice. However, more than 40% of patients with BRCA1/2 mutations are insensitive to PARP inhibitors, which has aroused the attention on the mechanism of PARP resistance and sensitization schemes. PARP inhibitor resistance is related to homologous recombination repair, stability of DNA replication forks, PARylation and epigenetic modification. Studies on epigenetics have become the hotspots of the research on PARP inhibitor resistance. As an important epigenetic regulator of transcription mediated by histone methylation, EZH2 interacts with PARP through DNA homologous recombination, DNA replication, post-translational modification, tumor immunity and other aspects. EZH2 inhibitors has been shifting from bench to bed-side, but the combination scheme in cancer therapy waits to be explored. Recently, a revolutionary drug design of the combination of PARP inhibitor and EZH2 inhibitor, based on PROTAC techniques, throw light on the resolution of PARP inhibitor resistance. This review summarizes the interactions between EZH2 and PARP, suggests the potential PARP inhibitor sensitization effect of EZH2 inhibitor, and further discusses the potential populations that benefit from the combination of EZH2 inhibitors and PARP inhibitors.